2020
DOI: 10.1590/1414-431x20209330
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-4290 suppresses PDK1-mediated glycolysis to enhance the sensitivity of gastric cancer cell to cisplatin

Abstract: The development of chemotherapy resistance significantly impairs the efficiency of chemotherapy, but the underlying mechanisms of chemotherapy resistance in gastric cancer (GC) are complicated and still need to be further explored. Here, we aimed to reveal the effects of miR-4290/PDK1 (pyruvate dehydrogenase kinase 1) axis on chemotherapy resistance of GC in vitro. The expression patterns of miR-4290 in GC tissues and cell lines were determined by real-time quantitative PCR. Kaplan-Meier was used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…PDK1, a downstream target of hypoxia inducible factor 1 alpha (HIF1a), is upregulated in a number of cancers including ovarian cancer (OCa) (36), gastric cancer (GCa) (37,38), colorectal cancer (CRCa) (39), PCa (40), and acute myeloid leukemia (AML) (41). Involvement of PDK1 has also been implicated in cancer cell epithelial-mesenchymal transition (EMT) and metastasis, for example in metastasis of liver aggressive 4T1 breast cancer (BrCa) cells to the liver, which implies an oncogenic role (12) ( Table 1).…”
Section: Pdk1-4 Levels In Different Cancers and Their Prognostic Implmentioning
confidence: 99%
See 1 more Smart Citation
“…PDK1, a downstream target of hypoxia inducible factor 1 alpha (HIF1a), is upregulated in a number of cancers including ovarian cancer (OCa) (36), gastric cancer (GCa) (37,38), colorectal cancer (CRCa) (39), PCa (40), and acute myeloid leukemia (AML) (41). Involvement of PDK1 has also been implicated in cancer cell epithelial-mesenchymal transition (EMT) and metastasis, for example in metastasis of liver aggressive 4T1 breast cancer (BrCa) cells to the liver, which implies an oncogenic role (12) ( Table 1).…”
Section: Pdk1-4 Levels In Different Cancers and Their Prognostic Implmentioning
confidence: 99%
“…PDK1-4 have been associated with therapy resistance in several cancers. Qian et al revealed that miR-4290 improved the sensitivity of GCa cells to cisplatin and induced apoptosis by downregulating PDK1 expression (38). Moreover, genetic knockdown of PDK1 abolished hypoxia-induced 5-fluorouracil (5-FU) resistance in GCa cells (74) and sensitized resistant OCa cells to cisplatin-induced cell death and apoptosis (75).…”
Section: Pdk1-4 Are Associated With Therapy Resistance In Several Canmentioning
confidence: 99%
“…Recent studies have demonstrated that combination treatment with some miRNAs is able to reduce the chemoresistance of cancers. [35][36][37][38] Among these miRNAs, miR-140 is reported to function as a tumor suppressor. [24][25][26] Furthermore, previous studies have indicated that miR-140 can enhance chemosensitivity of some cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant activation of PDK1 and its downstream effectors has been reported to involving in pathological phenotypes such as uncontrolled cell proliferation, apoptosis escape, invasion, and metastasis (Qian et al, 2020a), which may explain why HGC-27 cells showed higher metastatic ability in high serine administration in animal experiment. Some researches showed that PDK1 plays a role in chemoresistance in different types of malignancies, and targeting PDK1 could be a selection for promoting chemosensitization (Emmanouilidi and Falasca, 2017;Qian et al, 2020b). Recently, Yuan and colleagues reported that cryptotanshinone, originally a STAT3 inhibitor showed multiple suppressing activity on eight targets with anticancer potential, including MAP2K1, RARalpha, RXRalpha, PDK1, CHK1, AR, Ang-1 R, and Kif11 (Yuan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%